In situ cultured preantral follicles is a useful model to evaluate the effect of anticancer drugs on caprine folliculogenesis. Issue 8 (17th June 2016) - Guerreiro, Denise Damasceno; Lima, Laritza Ferreira de; Rodrigues, Giovanna Quintino; Carvalho, Adeline. de Andrade; Castro, Simone Vieira; Campello, Cláudio Cabral; Pessoa, Cláudia do Ó; Gadelha, Carla Renata Figueiredo; Figueiredo, José Ricardo de; Bordignon, Vilceu; Rodrigues, Ana Paula Ribeiro
ABSTRACT: Despite the increase in the incidence of cancer, the number of women who survive cancer treatment is growing. However, one of the principal results of chemotherapy is premature ovarian failure (POF). The aim of this study was to use the in situ culture preantral follicles as an in vitro model to evaluate the toxicity of two anticancer drugs, doxorubicin (DXR) and paclitaxel (PTX), on the integrity and development of ovarian follicles. Fragments of the ovarian cortex of goats were cultured in vitro for 1 or 7 days in α‐MEM + supplemented with different concentrations of DXR (0.003, 0.03, or 0.3 µg/mL) and PTX (0.001, 0.01, or 0.1 µg/mL). Analyses were performed before and after culture to evaluate tissue integrity by classical histology, apoptosis by TUNEL assay, DNA laddering kit and the detection of activated caspase 3, and DNA damage by the immune detection of phosphorylated histone H2A.x (H2AXph139). Both DXR and PTX reduced the number of morphologically normal primordial and developing follicles. Positive staining for TUNEL and active caspase 3 was detected in all the samples ( P  < 0.05). Therefore, we propose the in situ culture of caprine preantral follicles as a useful experimental model for assessing the toxic effects of the chemotherapeutic agents on ovarian folliculogenesis. Microsc. Res. Tech. 79:773–781, 2016 . © 2016 Wiley Periodicals, Inc.